2017
DOI: 10.1038/srep45278
|View full text |Cite
|
Sign up to set email alerts
|

Associations of parental age with health and social factors in adult offspring. Methodological pitfalls and possibilities

Abstract: Parental age is increasing rapidly in many countries. Analysis of this potentially important influence on offspring well-being is hampered by strong secular trends and socioeconomic patterning and by a shortage of follow-up data for adult offspring. We used Swedish national data on up to 3,653,938 offspring to consider the associations of parental age with a suite of outcomes in adult offspring, comparing the results from an array of statistical methods for optimal causal inference. The offspring of older moth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
32
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 61 publications
(83 reference statements)
1
32
0
Order By: Relevance
“…In daughters with low or normal childhood relative weight, birth to a teenage mother was associated with a higher risk of adult overweight and with slightly shorter stature, which may have partially mediated the association between mother's age at delivery and daughter's risk of preeclampsia. While the association with height is in agreement with previous reports, 19…”
Section: Principal Findingssupporting
confidence: 93%
See 1 more Smart Citation
“…In daughters with low or normal childhood relative weight, birth to a teenage mother was associated with a higher risk of adult overweight and with slightly shorter stature, which may have partially mediated the association between mother's age at delivery and daughter's risk of preeclampsia. While the association with height is in agreement with previous reports, 19…”
Section: Principal Findingssupporting
confidence: 93%
“…effect of advanced maternal age on offspring body weight, glucose metabolism, and blood pressure comes from a mouse study in which pups conceived by young and old dams were transferred into young surrogate mothers at the blastocyst stage. 18 In humans, it is reasonably well established that offspring of older mothers tend to be taller [19][20][21] and have a slightly higher risk of childhood type 1 diabetes (5% per 5-year increase in mother's age, according to a meta-analysis of 30 studies). 22 However, the evidence linking mother's age at delivery with offspring blood pressure, 19,[23][24][25][26] glucose metabolism, 20,27,28 and, especially, body mass index (BMI) [19][20][21][29][30][31][32][33][34] is mixed.…”
mentioning
confidence: 99%
“…Epidemiological and demographic studies in humans have shown a negative correlation between maternal age and children’s lifespan and health 25,27,30,45,46 . However, maternal age effects in humans can be difficult to separate from confounding environmental factors including paternal age effects, parental health, parental socio-economic status, and parental care 47-49 . Additionally, in human studies, both genotype and environment are usually uncharacterized, and it is impossible to systematically and simultaneously vary maternal age and offspring environment for a given genotype.…”
Section: Introductionmentioning
confidence: 99%
“…There was no association between a woman's mother's age at her birth and healthy survival to age 90, and parental ages were not associated with death before age 90 in this cohort of older women. Associations of parental ages with childhood and adulthood health outcomes among offspring have been mixed, and few studies have examined aging outcomes, such as exceptional longevity or healthy aging [4][5][6][7][8][9][10][11][12][13][14][15][16]. A prospective study among > 5000 adults ages 65 years and older observed no associations of parental ages with mortality or frailty in old age among sons or daughters [7].…”
Section: Discussionmentioning
confidence: 99%
“…Studies examining associations of parental ages at childbirth with offspring health outcomes have yielded inconsistent findings, and few studies have examined aging outcomes [4][5][6][7][8][9][10][11][12][13][14][15][16]. Some studies have linked older parental age at childbirth to outcomes including neurodevelopmental disorders, obesity, mortality, and morbidities including cancer among offspring in childhood and adulthood [4,[9][10][11][12]14].…”
Section: Introductionmentioning
confidence: 99%